2013
DOI: 10.5489/cuaj.961
|View full text |Cite
|
Sign up to set email alerts
|

Tumour location as a predictor of benign disease in the management of renal masses

Abstract: Objective: To investigate the association between tumour location and the proportion of benign disease in renal masses presumed to be renal cell carcinoma (RCC) preoperatively. Methods: This Institutional Review Board approved study includes 196 patients who underwent surgical treatment for renal masses <5 cm at our institution by a single surgeon between January 2002 and June 2009. Based on preoperative imaging, each mass was designated as central (touching or encroaching upon the renal collecting system and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…Tanto el análisis univariado como multivariado no mostró variables predictoras, excepto el tamaño por TAC, sin embargo, al establecer los grupos de riesgo por tamaño histológico se pierde el valor predictivo de esta variable. En otros estudios se han asociado con benignidad en la biopsia definitiva variables como localización y tamaño (tumores periféricos ≤ 5 cm son más benignos) 20 , sexo del paciente (femenino se asocia con benignidad) 21 , entre otras. Por su parte, está descrito que el porcentaje de tumores benignos aumenta con la disminución del tamaño tumoral 1 .…”
Section: Discussionunclassified
“…Tanto el análisis univariado como multivariado no mostró variables predictoras, excepto el tamaño por TAC, sin embargo, al establecer los grupos de riesgo por tamaño histológico se pierde el valor predictivo de esta variable. En otros estudios se han asociado con benignidad en la biopsia definitiva variables como localización y tamaño (tumores periféricos ≤ 5 cm son más benignos) 20 , sexo del paciente (femenino se asocia con benignidad) 21 , entre otras. Por su parte, está descrito que el porcentaje de tumores benignos aumenta con la disminución del tamaño tumoral 1 .…”
Section: Discussionunclassified
“…We have recently demonstrated that in this era of smaller, incidentally detected renal masses, tumour location has replaced tumour size as a predictor of benign disease. 13 We hypothesized that Management of small renal masses prediction of benign versus malignant disease may be as important as prediction of prognosis in the presence of a renal malignancy.…”
Section: The Nature Of Small Renal Massesmentioning
confidence: 99%